miR-182-mediated downregulation of BRCA1 impacts DNA repair and sensitivity to PARP inhibitors - Moskwa, Patryk; Buffa, Francesca M; Pan, Yunfeng; Panchakshari, Rohit; Gottipati, Ponnari; Muschel, Ruth J; Beech, John; Kulshrestha, Ritu; Abdelmohsen, Kotb; Weinstock, David M; Gorospe, Myriam; Harris, Adrian L; et al. (Molecular cell, 2011)
Expression of BRCA1 is commonly decreased in sporadic breast tumors, and this correlates with poor prognosis of breast cancer patients. Here we show that BRCA1 transcripts are selectively enriched in the Argonaute/miR-182 complex and miR-182 downregulates BRCA1 expression. Antagonizing miR-182 enhances BRCA1 protein levels and protects them from IR-induced cell death, while overexpressing miR-182 reduces BRCA1 protein, impairs homologous recombination-mediated repair, and render cells hypersensitive to IR. The impaired DNA repair phenotype induced by miR-182 overexpression can be fully rescued by overexpressing miR-182-insensitive BRCA1. Consistent with a BRCA1-deficiency phenotype, miR-182-overexpressing breast tumor cells are hypersensitive to inhibitors of poly (ADP-ribose) polymerase 1 (PARP1). Conversely, antagonizing miR-182 enhances BRCA1 levels and induces resistance to PARP1 inhibitor. Finally, a clinical-grade PARP1 inhibitor impacts outgrowth of miR-182-expressing tumors in animal models. Together these results suggest that miR-182-mediated downregulation of BRCA1 impedes DNA repair and may impact breast cancer therapy.